Brain glutamate in medication-free depressed patients: A proton MRS study at 7 Tesla - Godlewska, B; Masaki, C; Sharpley, A; Cowen, P; Emir, U (Cambridge University Press, 2017)
Background: The possible role of glutamate in the pathophysiology and treatment of depression is of intense current interest. Proton magnetic resonance spectroscopy (MRS) enables the detection of glutamate in the living human brain and meta-analyses of previous MRS studies in depressed patients have suggested that glutamate levels are decreased in anterior brain regions. Nevertheless, at conventional magnetic field strengths (1.5- 3 Tesla), it is difficult to separate glutamate from its metabolite and precursor, glutamine, with the two often being measured together as Glx. In contrast, MRS at 7 Tesla (7T) allows clear spectral resolution of glutamate and glutamine. Method: We studied 55 unmedicated depressed patients and 50 healthy controls who underwent MRS scanning at 7T with voxels placed in anterior cingulate cortex, occipital cortex and putamen. Neurometabolites were calculated using the unsuppressed water signal as a reference. Results: Compared to controls, depressed patients showed no significant difference in glutamate in any of the three voxels studied; however, glutamine concentrations in the patients were elevated by about 14% in the putamen (p< 0.001). Conclusions: The increase in glutamine in putamen is of interest in view of the postulated role of the basal ganglia in the neuropsychology of depression and is consistent with elevated activity in the descending cortical glutamatergic innervation to the putamen. The basal ganglia have rarely been the subject of MRS investigations in depressed patients and further MRS studies of these structures in depression are warranted.